Study of the inversion reaction of the lactonic fusion on eremanthine derivatives - Alves,José C. F. (2007)
The alpha-methylene-gamma-lactones 4(15)-dihydroeremanthine (8), 4(15),9(10)-tetrahydroeremanthine (9), isoeremanthine (10), allylic acetate delta1,10 (11), 1(R),10(R)-dihydromicheliolide (12) and 4alpha-hydroxy allylic acetate delta1,10 (13) were synthesized from the abundant natural product eremanthine (1). These substances were submitted to hydrolysis reaction with aqueous KOH and the carboxylic salts of these lactones had their hydroxy groups activated at the C-6 position by formation of respective mesylates (MsCl, Et3N, THF or DMSO) which underwent further displacement by carboxylate group. The utility of this methodology was investigated in order to obtain guaianolides with cis lactonic fusion at the C6-C7 position and to synthesize a precursor for posterior study of the biomimetic transformation of guaianolides into pseudoguaianolides.